2021
DOI: 10.3389/fpsyg.2021.558224
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Child Personality and Parenting in Relation to Child Well-Being: Support for Diathesis–Stress and Differential Susceptibility Patterns

Abstract: It is well-recognized that the individual characteristics of children moderate the effects of developmental conditions on the well-being of a child. The majority of interactions follow a diathesis–stress pattern; there is also evidence for differential susceptibility and vantage sensitivity models. The present study aimed to examine interactions between parenting and child personality in relation to the well-being of a Russian child and to evaluate the models for moderated relationships. Participants were prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The finding that emerging adults in the Resilient profile were distinguished by a combination of positive parenting of mothers and lower emotional stability and conscientiousness might seem puzzling. However, this pattern of findings aligns with the growing understanding that parenting behaviors and children's personalities interact in predicting developmental outcomes, exacerbating or buffering their effects (e.g., Loginova, & Slobodskaya, 2021;Pascual-Sagastizabal et al, 2021;Rioux et al, 2016). More specifically, in our study positive parenting behaviors of mothers may have buffered the potential negative effects of lower emotional stability and lower conscientiousness in the Resilient group.…”
Section: Discussionsupporting
confidence: 84%
“…The finding that emerging adults in the Resilient profile were distinguished by a combination of positive parenting of mothers and lower emotional stability and conscientiousness might seem puzzling. However, this pattern of findings aligns with the growing understanding that parenting behaviors and children's personalities interact in predicting developmental outcomes, exacerbating or buffering their effects (e.g., Loginova, & Slobodskaya, 2021;Pascual-Sagastizabal et al, 2021;Rioux et al, 2016). More specifically, in our study positive parenting behaviors of mothers may have buffered the potential negative effects of lower emotional stability and lower conscientiousness in the Resilient group.…”
Section: Discussionsupporting
confidence: 84%
“…For example, some evidence suggests that youth with relatively well-developed capacities for parasympathetic regulation display better adjustment in supportive family contexts, but not worse adjustment in unsupportive family contexts (Eisenberg et al, 2012;Van der Graaff et al, 2016). Consistent with a Diathesis Stress/DR framework, Loginova and Slobodskaya (2021) found that parenting style interacted with child temperament such that fearful temperament predicted greater adjustment problems in the context of punitive parenting but not better adjustment in the context of positive parenting. However, in the same sample, these researchers also found evidence of DS/BSC, wherein children who scored higher on a measure of personality flexibility/plasticity showed more adjustment problems in the context of punitive parenting, but fewer problems in the context of positive parenting.…”
mentioning
confidence: 78%